Respiratory infection rates differ between geographically distant paediatric cystic fibrosis cohorts. Issue 3 (26th September 2016) - Ramsey, Kathryn A.; Hart, Emily; Turkovic, Lidija; Padros-Goossens, Marc; Stick, Stephen M.; Ranganathan, Sarath C.
Respiratory infections are a major cause of pulmonary decline in children with cystic fibrosis (CF). We compared the prevalence of infection in early life at geographically distant CF treatment centres participating in the same surveillance programme in Australia. Lower airway microbiology, inflammation and structural lung disease at annual review were evaluated for 260 children 0–8 years old with CF at 1032 visits to CF treatment centres in Melbourne or Perth. Melbourne patients were more likely to be culture-positive for common respiratory pathogens at all age groups (odds ratio (OR) 1.85, 95% CI 1.33–2.58). Subjects <2 years old in Melbourne were also more likely to have neutrophil elastase present (OR 3.11, 95% CI 1.62–5.95). Bronchiectasis (OR 2.02, 95% CI 1.21–3.38) and air trapping (OR 2.53, 95% CI 1.42–4.51) in subjects 2–5 years old was more common in Melbourne subjects. The severity of structural lung disease was also worse in Melbourne patients >5 years old. Patients at both centres had a similar rate of hospitalisations and prescribed antibiotics. No procedural differences were identified that could explain the disparity between pathogen prevalence. Geographical differences in early acquisition of infection may contribute to variability in outcomes between CF centres. Infection rates different between two Australian paediatric cystic fibrosis patient cohorts http://ow.ly/PAmG302IYL4